Algebre

posted by .

simplify: {[3x^2+10x-8]/[5x-15]}/{[x^3+64]/[x^2-9]}

  • Algebra -

    Rewrite the following terms:
    5x-15 = 5(x-3)
    x^2-9 = (x+3)(x-3)
    3x^2 + 10x -8 = (x+4)(3x-2)
    x^3 +64 = (x+4)(x^2 -4x +16)
    Then cancel factors than appear in both numerator and denominator.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Math

    Simplify. (5x2 + 3x - 7) - (x2 - 7x + 4) Simplify. (5x^2 + 3x - 7) - (x^2 - 7x + 4) distribute - sign to get -x^2 +7x -4 put on top of one another and add 5x^2 + 3x - 7 -x^2 + 7x - 4 ------------- 4x^2 +10x -11
  2. Math -- not "can someone simplify this for me:10x-20 / x-2 "

    Repeated questions don't get you help faster. Please post only once. Thanks. can someone simplify this for me:10x-20 / x-2 first factor x-2 out of the numerator to get (x-2)10 -------- (x-2) Now cancel the (x-2) to get you answer of …
  3. Math

    Find the equation of the tangent line 5x^2+y^2=14 at (1,3). P.S: It's calculus. So far I know this much 10x+2y(dy/dx)=o -10x -10x ___________________ 2y(dy/dx)= -10x (dy/dx)= -10x/2y= -5x/y m= -5(1)/3= -5/3 y=mx+b 3= -5/3(1)+b then …
  4. Intermediate Algebra

    I have a take home test and I'm stuck on a couple. Anyone help please?
  5. Math

    Can someone please check my answers below for accurateness?
  6. Math!

    1) What is the value of 19 + 5a^4 + 3b^2 when a = 2 and b = -4?
  7. Math

    Simplify the expression. 3x + 4(x - 6) - 3(x - 7) A. 4x - 45 B. 4x - 3 C. 10x - 3 D. 10x + 45 Is it b?
  8. Algebra

    equations and inequalities unit test for questions 1-5, solve the equation 4. 3(4-2x)=-2x (1 point) a. -1*** b. 1 c. 2 d. 3 5. 5.4+0.2x=-1.4x+8.6 a. 2 b. -2 c. .2*** d. 20 For questions 6-7, simplify the expression 6. -4 - 5(x+8) a.-5x …
  9. Algebra

    Simplify. 2/3a * 2/a^2 A. 4/3a^2; where a =/= 0 B. 1/a^2; where a =/= 0 C. 4/3a^3; where a =/= 0** D. 4/3a^2 Multiply. X+2/5x-15*(10x^2-25x-15) A. (2x+1)/5(x-3) B. (2x+1)(x-3)/5** C. (10x+5)(x+2) D. (X+2)(2x+1)
  10. Math

    5.Simplify x/6x-x^2 a)1/6-x ; where x=0.6 b) 1/6-x; where x=6*** c)1/6x; where x=0 d)1/6 6. 5x^3/7x^3+x^4 a)5/7+x; where x= 0,-7**** b)5/7+x; where x=-7 c)5/7x; where x=0 d)5/7 7.x-2/x^2+4x-12 a)1/6+x; where x=-6*** b)1/6+x; where …

More Similar Questions